Study on the photoacoustic spectroscopy measurement of methane with different laser bias DC waveforms - Mengqi, Li; Zhengguang, Chen; Jie, Wang; Haohao, Qin; Zhenqin, Zhou; Siqi, Huang; Qiaohua, Wang (Frontiers in Energy Research, 2025)
In dissolved gas analysis of transformers, methane is one of the key indicators for fault diagnosis, thus accurate methane detection means a lot for early transformer failure caused by partial discharge or overheat. Photoacoustic Spectroscopy (PAS) combined with Tunable Diode Laser (TDL) as light source, is to provide high precision and selectivity in gas measurement, especially in conditions of trace gas measurement with limited light length and sample volume. By constructing an experimental platform, the intensity, linearity, and stability of photoacoustic signals under different bias DC waveforms (sawtooth wave, triangle wave, and sine wave) were compared and analyzed. The experimental results indicate that different bias DC waveforms have a significant impact on the photoacoustic signal. With sine wave configuration the system achieves the best measurement performance and accurate methane measurement (under 1.4 s integrated time, the detection limit 0.2 ppm) and meets the requirement of on-line dissolved gas analysis (DGA) for transformers.